Biomass Potential from Agricultural Residues in Indonesia - Fathimah Azzahra; Haydar Hacıseferoğulları (Hasanuddin University, 2026)
Biomass can serve as an alternative to fossil fuel consumption which causes significant harm to the environment and human health. Indonesia, being an agricultural country, possesses a substantial biomass energy potential. This study aimed to estimate the biomass potential derived from major food and plantation crops in over the past five years and present its distribution map across the country’s 38 provinces. Residues from paddy, corn, sugarcane, coconut, and oil palm are considered. The estimation of biomass potential from agricultural residues was calculated based on the average of 2020-2024 production data of related crops using equations from previous literatures. As a result of the study, the total available agricultural biomass residue potential (ABP) from these five crops residues was calculated to be 55.79 million tons, with a total heating value (THV) of approximately 857.44 PJ. The biomass potential from paddy, corn, and oil palm residues holds the highest value, approximately 98.23% (842.31 PJ) of the total estimated biomass potential. Among food crops, provinces with the highest biomass potential from paddy residues are East Java, Central Java, and West Java, while from corn residues, East Java and Central Java are prominent. For plantation crops, East Java and Lampung lead in biomass potential from sugarcane residues; Riau and North Sulawesi from coconut residues; also Riau, Central Kalimantan, and West Kalimantan from oil palm residues. It is expected that this study will contribute to the development of biomass energy utilization from agricultural residues in each province in Indonesia and that enhancing biomass availability could further promote sustainable agriculture and energy management in Indonesia.